Pharmaceutical/Clinical Strategies in the Treatment of Acute Promyelocytic Leukemia: All-Trans Retinoic Acid Encapsulation by Spray-Drying Technology as an Innovative Approach-Comprehensive Overview - Antónia Gonçalves; Fernando Rocha; Berta N. Estevinho (MDPI AG, 2023)
Acute promyelocytic leukemia (APL) is phenotypically characterized by the accumulation of dysplastic promyelocytes, resulting from a cytogenetic condition due to the balanced chromosomal translocation t(15;17)(q22;q21). Current first-line treatment of APL includes all-trans retinoic acid (all-trans RA), with or without arsenic trioxide, combined with chemotherapy, and a chemotherapy-free approach wherein arsenic trioxide is used alone or in combination with all-trans RA. The usage of all-trans RA revolutionized the treatment of APL, with survival rates of 80 to 90% being achieved. The mechanism of action of all-trans RA is based on regulation of gene transcription, promoting the differentiation of leukemic promyelocytes. Encapsulation technology has been explored as an innovative strategy to overcome the major drawbacks related to the all-trans RA oral administration in the APL treatment. The most recently published works on this subject highlight the development and optimization of carrier-based delivery systems based in microparticle formulations obtained by spray-drying to be used in the treatment of APL. The ultimate goal is to obtain a controlled delivery system for RA oral administration capable of providing a slow release of this bioactive compound in the intestinal lumen.